NSW Workers' Compensation Reform: A Parody of Evidence‐based Policy Making. Issue 2 (30th January 2015) - Holley, Sasha; Thornthwaite, Louise; Markey, Ray; O'Neill, Sharron
Abstract : The characteristics and evolution of evidence‐based policy making in Australia and other mature democracies have been mapped extensively in this journal. This article advances research on the use of evidence in policy making, examining changes in the New South Wales workers' compensation system from 2012 to 2014. This analysis of two phases of policy change, legislative implementation and statutory review, highlights the limitations of building integrated, coherent evidence‐based policy in a contentious policy area. The article finds that the collection of wide and detailed evidence will not satisfy requirements of evidence‐based policy without political will, transparency, and accountability. Abstract : This article advances research on the use of evidence in policymaking through examining changes to the New South Wales workers' compensation system since early 2012. The analysis highlights the limitations of building integrated, coherent evidence‐based policy in a contentious policy area.